Organically Modified Montmorillonite as Nanoreactor to Improve the Grafting Degree of Maleic Anhydride onto Polypropylene - Zhenghui Li; Peijie Yu; Lu Chen; Lingli Zhang; Hongyu Hu (Journal of Chemistry)
The application of an organically modified montmorillonite nanoreactor in the reactive extrusion process of the free radical grafting of maleic anhydride onto polypropylene (PP) can increase the MAH grafting degree on the PP. The mechanism of grafting was studied by using transmission electron microscopy and high temperature gel permeation chromatography. It was found that both the strong interactions between MAH and MMT surface and the encapsulation effect of active species confined in o-MMT improved the grafting degree.